Semi-stochastic generation of rock discontinuity networks based on traces exposed on cavern roof. (January 2022) - Zhang, Qi-Hua; Liu, Qing-Bing
Abstract: The rapid development of digital mapping technologies such as terrestrial laser scanning, digital photogrammetry has allowed the exact acquisition of superficial information of discontinuities in rock exposures. Nevertheless, it remains challenging to quantify the spatial dimension and areal persistence of discontinuities due to the impossibility of direct observation of complete extent of discontinuities in three dimensions. The difficulties of characterizing individual discontinuities deterministically lead to the development of stochastic 3-D discontinuity networks. The stochastic modeling scheme are based on the statistical analysis of the measured discontinuity parameters; hence, the generated discontinuity networks represent discontinuity system in a statistical sense, and in most cases, the discontinuity traces formed by stochastic model are inconsistent with those observed at rock outcrops. To deal with this issue, this study presented a new method to simulate discontinuity network, which employs the real traces exposed on the cavern roof as the constraint condition of stochastic modeling and is described herein as semi-stochastic. The method takes discontinuities as circular discs and establishes geometrical relationship between the radius and the center of circular disc respectively for three classes of traces (i.e. trace has two ends, only one end, and neither end, visible in the sampling window). A case study with the proposed method shows that the traces yielded by the intersections of modeled discontinuity network with the cavern roof are in close agreement with actual situation. This semi-stochastic method further improves conventional stochastic modeling technique in terms of enabling a more realistic representation of rock discontinuities.